Variability within IGF1 and its linkage to body size and predisposition to hip dysplasia in dogs - FROST, ANNA; PROSKURA, W S; BARNIK, J; SZATKOWSKA, I; DYBUS, A (The Indian Journal of Animal Sciences, 2015)
Insulin-like growth factor (IGF) plays a very important role in development and functioning of joints, and is also considered as one which may be linked to body size in domestic dogs (Canis familiaris). The aim of this study was to establish if there is an association of g.41221438A>G SNP within insulin-like growth factor-1 gene (IGF1) with determination of body size and with predisposition to hip-dysplasia in domestic dogs. There was a significant difference of genotypes distribution between groups of small and large dogs (P<0.001) and also between groups of individuals predisposed and non-predisposed to hip dysplasia (P<0.001). On the basis of this research we propose g.41221438A>G single nucleotide polymorphism as a very interesting candidate for genetic marker of both body size and predisposition to hip-dysplasia in dogs.